Colour Identity in Urban Place: Highcross - Johnny Xu (2018)
This video-documentation is an edition combining interviews and visual research. The interview transcripts explain why certain colour can be seen as identity related to particular place, whereas the visual captures what colour appearance exist in its urban context.